Features of Positivism in the Researches of Social Deviances - Jugović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The subject of this article is a critical analysis of the features of the positivist approach in the research on social deviances. The article explains key theoretical and methodology concepts of positivism in the field of social pathology as a science about social deviances. The aim of this paper is to demonstrate the importance and specificity of positivist influence on the explanation of social deviances. This paper highlights some aspects of phenomenology, methodology and axiology of positivism in the research on social deviances. Specifically, in this paper, the importance of a positivist view on the relationships between man and society is emphasised in the explanation of social deviances. The main conclusion is that the methodology of positivism in the research on social deviances ignores individual subjectivity, social conflicts and qualitative methods.